2016
DOI: 10.1038/srep23940
|View full text |Cite
|
Sign up to set email alerts
|

High mobility and high stability glassy metal-oxynitride materials and devices

Abstract: In thin film technology, future semiconductor and display products with high performance, high density, large area, and ultra high definition with three-dimensional functionalities require high performance thin film transistors (TFTs) with high stability. Zinc oxynitride, a composite of zinc oxide and zinc nitride, has been conceded as a strong substitute to conventional semiconductor film such as silicon and indium gallium zinc oxide due to high mobility value. However, zinc oxynitride has been suffered from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…3 In contrast to the conventional AOSs, amorphous ZnO x N y is an alloy of an oxide (ZnO, wurtzite) and a nitride (Zn 3 N 2 , anti-bixbyite) that have the same cation. A remarkable feature of amorphous ZnO x N y is its high electron Hall mobility, over 100 cm 2 V À1 s À1 , [4][5][6] which is comparable with the highest reported values for AOSs. 7,8 However, more recent studies using transmission electron microscopy (TEM) and electron diffraction revealed that these "amorphous" ZnO x N y thin films contained nanocrystals of ZnO and Zn 3 N 2 , 4 which would reduce their mobility through grain boundary scattering.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…3 In contrast to the conventional AOSs, amorphous ZnO x N y is an alloy of an oxide (ZnO, wurtzite) and a nitride (Zn 3 N 2 , anti-bixbyite) that have the same cation. A remarkable feature of amorphous ZnO x N y is its high electron Hall mobility, over 100 cm 2 V À1 s À1 , [4][5][6] which is comparable with the highest reported values for AOSs. 7,8 However, more recent studies using transmission electron microscopy (TEM) and electron diffraction revealed that these "amorphous" ZnO x N y thin films contained nanocrystals of ZnO and Zn 3 N 2 , 4 which would reduce their mobility through grain boundary scattering.…”
supporting
confidence: 71%
“…In the previous studies, [3][4][5][6] ZnO x N y thin films were fabricated by reactive sputtering. However, sputtering frequently causes unintentional substrate heating 9,10 and collisions of high-energy particles with the film surface during deposition, which would induce crystallization of the film.…”
mentioning
confidence: 99%
“…However, it is claimed that due to the presence of multiple cations of different ionic sizes, the electronic conduction path is hindered, which limits the carrier mobility 29 . As an alternative to multi-cation amorphous metal oxides, a multi-anion approach towards amorphous semiconductors has been proposed and is being investigated experimentally and computationally [29][30][31][32][33][34][35][36] . Amorphous zinc oxynitride (a-ZnON), as a multi-anion amorphous semiconductor, has shown a great promise as a viable replacement of a-IGZO and the electron mobilities (Hall mobilities) exceeding 200 cm 2 /V.s have been experimentally reported 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Novel physical properties of oxynitride thin films have been the center of extensive investigations due to their properties and the potential applications in a wide range of electronic and optoelectronic devices. For example, monometallic and bimetallic oxynitrides have been investigated as catalysts [1], lithium phosphorus oxynitrides have been applied in thin film lithium ion batteries [2], titanium oxynitride has been developed for optical hard coatings [3], titanium niobium oxynitride has been applied in photocatalysis [4], indium and indium tin oxynitrides have been used for specific applications like gas sensors and high temperature thin film thermocouples [5,6], aluminum oxynitride has been applied as transparent and conductive layers in optoelectronic devices [7], and zinc oxynitrides have been conceded as a strong substitute to conventional semiconductor film such as silicon due to high mobility value [8,9]. In this context, as general rule, amorphous oxynitrides have much higher charge carrier mobility than a-Si [10][11][12].…”
Section: Introductionmentioning
confidence: 99%